A peptide tag-specific nanobody enables high-quality labeling for dSTORM imaging - David Virant (Nature Portfolio, 2018)
Nanobodies (Nbs) coupled to organic dyes are increasingly used for super-resolution cell imaging, but producing gene-specific Nbs is time-consuming. Here the authors present a peptide-tag/Nb combination for dSTORM imaging which can be easily adapted to different targets in fixed and live cells.